Ocean Policies and Institutional Arrangements for Cross-sectoral Cooperation: Case studies for achieving Sustainable Development Goals - UNEP Regional Seas Report and Studies No. 204 - United Nations Environment Programme (2020)
The case studies include: i) Delivering the Mediterranean Strategy for Sustainable Development 2016-2025 through a highly inclusive process to transpose Agenda 2030 and its sustainable development goals at the regional level; ii) Fostering cooperation in the Mediterranean and the Black Sea in the context of Strategic Development Goal 14: Ongoing efforts promoted by the General Fisheries Commission for the Mediterranean of the Food and Agriculture Organization of the United Nations (GFCM); iii) HELCOM cross-sectoral cooperation and partnerships on clean and safe Baltic Sea shipping; iv) Regional co-operation on marine pollution preparedness and response in the Northwest Pacific Region; v) Cooperation in the Danube-Black Sea Basin: Example of the Commission on the Protection of the Black Sea Against Pollution (Black Sea Commission) and the International Commission for the Protection of the Danube River (ICPDR); vi) 2050 Africa’s Integrated Maritime Strategy and African Ocean Governance Strategy; vii) Update on the design of an integrated regional ocean policy for the Permanent Commission for the South Pacific; viii) Potential cooperation between the Regional Organization for the Protection of the Marine Environment (ROPME) and the Regional Commission for Fisheries (RECOFI); ix) Cooperation between the Abidjan Convention and the Sub-Regional Fisheries Commission; and x) OSPAR cooperation with the North East Atlantic Fisheries Commission (NEAFC) and other relevant intergovernmental organizations, with particular reference to area-based management.